Influence of FSES input on personnel policy in educational institutions - Koltasheva Y. D. (Educational environment today: development strategy, 2016)
the successful introduction of the federal state educational standart requires high-qualified administrative and teaching staff. The main directions and objectives are development and implementation of unified reforms, monitoring of progress, providing of resource maintenance.
Keywords: эффективность; введение; управление образовательным процессом; подготовка педагогических кадров; effectiveness; educational management; инновационная стратегия; personnel training; federal state educational standart induction; innovative strategy; подготовка управленческих кадров